Objective Daily Maps of Thermocline Depth for the SYNOP Eastern Array - Hallock, Z. R. (1992)
A major component of the field activities for the northwest Atlantic Regional Energetics Experiment (REX) is focused on the acquisition and analysis of data from inverted echo sounders (IESs). This technical note describes an analysis of data records from nine lESs deployed in an array near 4O'N, 55'W. IES acoustic travel-time data were converted to thermocline depths, which were in turn objectively interpolated and contoured, resulting in daily maps. These maps provide a useful tool for studying the evolution of mesoscale features in the area of the experiment.